2013
DOI: 10.1121/1.4776775
|View full text |Cite
|
Sign up to set email alerts
|

Coherent processing of shipping noise for ocean monitoring

Abstract: Ambient noise was recorded on two vertical line arrays (VLAs) separated by 450 m and deployed in shallow water (depth ~150 m) off San Diego, CA continuously for 6 days. Recordings were dominated by non-stationary and non-uniform broadband shipping noise (250 Hz to 1.5 kHz). Stable coherent noise wavefronts were extracted from ambient noise correlations between the VLAs during all 6 days by mitigating the effect of discrete shipping events and using array beamforming with data-derived steering vectors. This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 12 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Passive fathometer applications are a special case, corresponding to effectively 1-D (vertical) propagation, which have proven to be successful [Siderius et al, 2006[Siderius et al, , 2010Gerstoft et al, 2008]. There have also been several successful demonstrations at horizontal separations ranging from a few hundred meters [Fried et al, 2008;Brooks and Gerstoft, 2009;Fried et al, 2013;Lani et al, 2013] to 3.5 km [Roux et al, 2004;Sabra et al, 2013]. Additionally, Godin et al [2010] have successfully demonstrated the feasibility of passive acoustic tomography by retreiving the sound speed from moored mid-ocean noise measurements with horizontal separations of 0.5 to 3.5 km.…”
Section: Introductionmentioning
confidence: 99%
“…Passive fathometer applications are a special case, corresponding to effectively 1-D (vertical) propagation, which have proven to be successful [Siderius et al, 2006[Siderius et al, , 2010Gerstoft et al, 2008]. There have also been several successful demonstrations at horizontal separations ranging from a few hundred meters [Fried et al, 2008;Brooks and Gerstoft, 2009;Fried et al, 2013;Lani et al, 2013] to 3.5 km [Roux et al, 2004;Sabra et al, 2013]. Additionally, Godin et al [2010] have successfully demonstrated the feasibility of passive acoustic tomography by retreiving the sound speed from moored mid-ocean noise measurements with horizontal separations of 0.5 to 3.5 km.…”
Section: Introductionmentioning
confidence: 99%
“…This symmetry of the arrival time variations demonstrates that they are due to reciprocal changes in the environment, such as ocean sound speed fluctuations induced by temperature changes, rather than nonreciprocal changes, such as currents, clock drift, or other signal-processing artifacts [Sabra et al, 2005b;Lani et al, 2013]. The symmetric arrival time variations could not be established for the Ascension Island site due to the African continent blockage of ocean noise propagating southward.…”
Section: 1002/2015gl063438mentioning
confidence: 85%
“…There is a high degree of similarity of the arrival time variations obtained for both the positive and negative time delay arrivals (Figure 2c) which result from different noise events propagating northward or southward, respectively, along the same paths linking the south and north triads for the Wake Island site. This symmetry of the arrival time variations demonstrates that they are due to reciprocal changes in the environment, such as ocean sound speed fluctuations induced by temperature changes, rather than nonreciprocal changes, such as currents, clock drift, or other signal-processing artifacts [Sabra et al, 2005b;Lani et al, 2013]. The symmetric arrival time variations could not be established for the Ascension Island site due to the African continent blockage of ocean noise propagating southward.…”
Section: Passive Acoustic Thermometry Of the Deep Oceansmentioning
confidence: 96%
“…Other technical features of the hydrophone array deployment and the electronic system have been described previously. [33][34][35] The research vessel (R/V) New Horizon was used as a surface source of opportunity to test the myopic deconvolution method using the recorded shipping noise data on the VLA. Since no ground truth was available for the actual CIR between the R/V and the VLA, estimated CIRs from the myopic deconvolution were compared to the estimated CIRs independently obtained using a previously described RBD method.…”
Section: Deconvolution Of Experimentally Measured Shipping Noise Rmentioning
confidence: 99%
“…To do so, K ¼ 16 CIRs between the R/V and the VLA were first estimated using RBD for an arbitrarily selected location of the R/V %600 m away from the VLA, referred to hereafter as the "library" location. Based on visual inspection of spectrograms of the recorded shipping noise 34,35 from the R/V at this distance, its dominant frequency band was found to be 300-800 Hz and the 10-s long snapshot of recorded data was filtered in this frequency band. These K ¼ 16 estimated CIRs with RBD [see Fig.…”
Section: Deconvolution Of Experimentally Measured Shipping Noise Rmentioning
confidence: 99%